ISLAMIC ESG: RESEARCH PROGRESS AND FUTURE PROSPECTS - Salin, Ahmad Saiful Azlin Puteh; Ali, Nurul Badriyah (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
The purpose of this study is to provide a descriptive overview and depicts the current and future trend of research in Islamic ESG. Bibliometric analysis is used to objectively scrutinize the bibliographic data collected from the Scopus database. Various methodologies and approaches are used to provide the results for research topics, impacts and directions, as well as patterns of collaboration. This study examines how the Islamic ESG has evolved between 2012 and 2023. This study finds that the publications increase significantly from 2021. Corporate governance, corporate social responsibility, environmental, sustainability, sustainable development, Islamic banks, Islamic corporate finance and Islamic finance are among the popular research and collaboration trends found in the extant literature, reflecting the multidimensional nature of ESG research within the Islamic context. Malaysian authors published more articles followed by authors from Indonesia and Italy. Based on this, several key research gaps and further suggestions are acknowledged for future studies. This is original as compared to the existing bibliometric literature, this study is among the pioneer wide ranging bibliometrics study on Islamic ESG. The request to have a specific model of ESG that complies with Shariah and aligns with Islamic teaching in the future cannot be underestimated, knowing that the Muslim community right now has exceeded two billion worldwide. This study is beneficial to potential researchers, scientific journal editors, practitioners, policy makers and students to understand the current research progression and evolution of ESG from an Islamic perspective.